Ecotourism and Biodiversity Conservation: Paradigm Shifting and Future Action - Ardiansyah, Rhomi; Yusmur, Armaiki; Marlinda, Shella; Supriyanto; Bigcas, Evelyn V. (BIODIVERS - BIOTROP Science Magazine, 2023)
Tourism has been positively impacting the economy for decades. However, the industry has also brought several challenges related to climate change and biodiversity conservation. This paper will discuss tourism's issues, trends, and future perspectives supporting biodiversity conservation.